2021
DOI: 10.1016/j.jad.2020.09.080
|View full text |Cite
|
Sign up to set email alerts
|

Depressed, anxious, and stressed: What have healthcare workers on the frontlines in Egypt and Saudi Arabia experienced during the COVID-19 pandemic?

Abstract: Highlights HCWs in Egypt and Saudi-Arabia experienced depression, anxiety, and stress during the COVID-19 pandemic. Female sex, age ≤30 years, attending night shifts, and watching/reading COVID-19 news associated with worse psychological disturbances. Providing psychological support to HCWs during the COVID-19 pandemic is an urgent need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
150
9
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(188 citation statements)
references
References 36 publications
(39 reference statements)
23
150
9
6
Order By: Relevance
“…Forty-nine studies originated from China, four from each Turkey and Iran, three from Italy, two each from Germany, Jordan, Nepal, Pakistan, Spain, the USA and the UK, and one from each of the following: Austrian, Bahrain, Croatia, Egypt, Ethiopia, France, Greece, Korea, Kosovo, KSA, Malawi, Mongolian, Poland, Portugal, Russia, Singapore and Switzerland. Two study was conducted in more than one country [ 38 , 39 ]. (See Table 1 for a general characteristics of studies).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Forty-nine studies originated from China, four from each Turkey and Iran, three from Italy, two each from Germany, Jordan, Nepal, Pakistan, Spain, the USA and the UK, and one from each of the following: Austrian, Bahrain, Croatia, Egypt, Ethiopia, France, Greece, Korea, Kosovo, KSA, Malawi, Mongolian, Poland, Portugal, Russia, Singapore and Switzerland. Two study was conducted in more than one country [ 38 , 39 ]. (See Table 1 for a general characteristics of studies).…”
Section: Resultsmentioning
confidence: 99%
“…Stress was estimated in 40 studies [ 18 , 20 , 25 , 27 , 29 , 33 , 35 , 36 , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] ]. The overall pooled point estimates of prevalence for stress varied between 10% and 84% ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased stress levels among HCWs in fever clinics who were on the frontlines during the COVID-19 pandemic came in line with previous national and international studies assessing stress among similar study populations. In a study conducted on 426 HCWs from Saudi Arabia and Egypt (48.4% physicians, 24.2% nurses and 27.4% other HCWs) on the frontlines fighting COVID-19, more than half (55.9%) of them had stress [55]. Another study conducted on 5062 HCWs (19.8% physicians, 62.2% nurses and 18.0% technicians) treating patients with COVID-19 in China showed that 29.8% of participants had stress [56].…”
Section: Discussionmentioning
confidence: 99%